Vulnerable populations: A cross-case synthesis of correctional facility disaster response during Hurricanes Katrina and Maria - Dement, BA (Hons), MA, Carl; McAleavy, BA (Hons), MSc, PhD, Tony (Journal of Emergency Management, 2021)
Objective: This study aims to critically evaluate the Orleans Parish Prison (OPP), New Orleans, Louisiana response to Hurricane Katrina in 2005 and the Metropolitan Detention Center (MDC), Guaynabo, Puerto Rico, response to Hurricane Maria in 2017 to determine key areas for policy development. Design: This study uses an interpretivist paradigm to conduct an inductive, cross-case synthesis and content analysis. Setting: The OPP in Katrina and the MDC in Maria; case-studies determined by similar exposure to hurricanes in the Caribbean and inmate population. Subjects: Inmates as an intrinsically vulnerable population. Interventions: Cross-case synthesis of the two selected case-studies comparing response to separate hurricanes. Main outcome measure(s): The ProQuest, Wiley, Scopus, Science Direct, and Google Scholar databases were used to establish a corpus of qualitative data focused on the evacuation and humane treatment of inmates. Inductive content analysis resulted in three themes which informed seven policy recommendations for enhanced correctional facility preparedness for natural and human-induced hazards. Results: The preparedness of correctional facilities remains inadequate despite significant experience during Katrina, Maria, and other disasters demonstrating a failure in isomorphic learning. Conclusions: The theoretical contributions of this study are encapsulated in seven recommendations. Three are recommended accountability and support measures for the BOP and state institutions by involving the FEMA and the GAO. The other four are recommended improvements in EM planning for counties and municipalities.